Micellar formulations of Crizotinib and Dasatinib in the management of glioblastoma multiforme. (14th September 2018) - Greish, Khaled; Jasim, Anfal; Parayath, Neha; Abdelghany, Sara; Alkhateeb, Ali; Taurin, Sebastien; Nehoff, Hayley
Abstract: Glioblastoma multiforme (GBM) defies the currently practiced management of radiotherapy, chemotherapy and surgery and hence, it is associated with a high fatality rate with a median survival of 14.6 months. In our previous work investigating different tyrosine kinase inhibitors (TKIs), we established that a combination of Crizotinib and Dasatinib exerted the most potent effect on different GBM cell lines. In this work, to improve targeted therapy at the site of the tumour and avoid systemic toxicity, we exploited the enhanced permeability and retention effect by designing micellar formulations of these two TKIs. Crizotinib and Dasatinib were successfully encapsulated in poly(styrene-co-maleic acid) (SMA) micelles which were then evaluated for their physicochemical characteristics, anti-proliferative effect, mode of cell death, efficacy in spheroid models, effect on cell signalling, antiangiogenic potential and in vivo anticancer activity. Our results showed that this combination had induced a potent anti-proliferative effect in four GBM cell lines grown as a monolayer and as a spheroid. The combination was also efficacious in in vitro models of angiogenesis and vascular mimicry. In vivo data showed the enhanced activity of the micellar TKIs compared to free drugs. In conclusion, we proved that micellar formulations of Crizotinib and Dasatinib carry promising in vitro and in vivo efficacy that warrant further investigation.